An updated checklist of Echinoderms from Indian waters - Samuel, Vijay Kumar Deepak; Krishnan, Pandian; Sreeraj, Chemmencheri Ramakrishnan; Chamundeeswari, Kanagaraj; Parthiban, Chermapandi; Sekar, Veeramuthu; Patro, Shesdev; Saravanan, Raju; Abhilash, Kottarathil Rajendran; Ramachandran, Purvaja; Ramesh, Ramachandran (Zootaxa, 2017)
Species checklists enlist the species available within the defined geographical region and thus serve as essential input for developing conservation and management strategies. The fields of conservation biology and ecology confront the challenge of inflated biodiversity, attributed to non-recognition of taxonomic inconsistencies such as synonyms, alternate representation, emendations etc. Critical review of the checklists and distributional records of Phylum Echinodermata from Indian waters and subsequent validation of species names with World Register of Marine Species (WoRMS) database, revealed that the current literature included 236 incorrect entries comprising of 162 synonyms, 15 emendations, 5 nomina dubia, 1 nomen nudum, 40 species under alternate representation, 9 species with author misnomer, 1 subspecies and 1 unaccepted. The 226 species found to be mixed with valid names and a revised checklist was prepared. The revised and updated checklist holds 741 species of echinoderms comprising of 182 asteroids (24.56%), 70 crinoids (9.45%), 138 echinoids (18.62%), 179 holothuroids (24.16%) and 172 ophiuroids (23.21%), placed under 28 orders and 107 families. This paper discusses the cause for taxonomic inflation and argues that such taxonomic inconsistencies alter our interpretations of a species including its inaccurate distribution and, could possibly impede the country’s conservation and management efforts.